Det multimodale ikon - Conte, Joseph M. (Passage - Tidsskrift for litteratur og kritik, 2013)
I den indledende artikel af Joseph M. Conte, “Det multimodale ikon: Syn, lyd og kognition i nyere poesi”, opridses poesiens historie frem til i dag med udgangspunkt i den tese, at der er sket et skift i den måde, hvorpå vi afkoder poesi. Mens man tidligere opfattede poesi som en kunstart, der kun udtrykte sig i én kode, nemlig bogstaverne på bogsiden, er digtet i den digitale tidsalder blevet et multimodalt ikon, i hvilket tekst og billede samvirker i betydningsdannelsen på en kompleks måde. Hvis fortolkeren skal være på højde med den nyeste poesi, kræver det ifølge Conte således også nye tilgange og kompetencer. Joseph M. Conte: “The Multimodal Icon: Sight, Sound and Intellection in Recent Poetries” This article examines the shift from single to multiple semiotic modes in poetry during the age of digital media. While one can argue that in the history of poetry the text has always represented “sight, sound and intellection,” the propagation of digital media and the devolution of popular culture into a predominantly graphical regime have made an irrevocable impression on poetry on-the-page. The production of multimodal poetry in print literature presents the hybridization of text and image, or typography and the visual arts. In the multimodal poetry of Emily McVarish, Steve McCaffery and Geof Huth, the reader encounters two or more semiotic modes simultaneously. The relation between text and image is not one of dependency or autonomy but rather a bilateral interactivity that requires and stimulates a cognitive poetics. Such print works demand that readers pursue a multiplicity of reading paths and develop the interpretive skills required by multimodal metaphor in which signs are drawn from more than one mode.